KAJIAN MORFOMETRI RANU GRATI MENGGUNAKAN GPSMAP 585 DAN SIG - Darmawan, Arief; Mahmudi, Mohammad; Nisa, Tisya Wahidatun; Putri, Cesarlia Dwi Sulestyanar; Gurinda, Gita Adistri; Putri, Amelia Wahyuning (OLDI (Oseanologi dan Limnologi di Indonesia), 2019)
Ranu Grati?s Morphometry Study Using GPSMAP 585 and GIS. In the study of pollution load capacity of a reservoir or lake, its required information such as innudation area, average of depths and innudation volume, but those data at sometimes unavailable and out of date. The aims of this research are to find out depth distribution in Ranu Grati and represent it on a map. Depth map or bathymetry map that resulted is show morphological condition that can be used for further study e.g calculation of Ranu Grati capacity for aquaculture. Area of inundation, inundation volume and average depth of Ranu Grati can be figured out by using Garmin GPSMAP 585, Sentinel 2a imagery, BingMap and GIS analysis with ArcGIS according to those mapping data. Visualization of the mapping result through 3D view is used to increase understanding Ranu Grati morphometric conditions such as for Ranu Grati carriying capacity for aquaculture etc.. The result shows maximum depth that recorded during mapping is 121, 9 m. Meanwhile, area of inundation and volume are 1.734.223,07 m2 and 124.491.952,55 m3 respectively.